2009
DOI: 10.1530/eje-08-0669
|View full text |Cite
|
Sign up to set email alerts
|

Low-activity (2.0 GBq; 54 mCi) radioiodine post-surgical remnant ablation in thyroid cancer: comparison between hormone withdrawal and use of rhTSH in low-risk patients

Abstract: Objective: (a) To compare the efficacy of low-activity (2 GBq; 54 mCi) 131 I ablation using L-thyroxine withdrawal or rhTSH stimulation, and (b) to assess the influence of thyroid remnants volume on the ablation rate. Design: Patients underwent neck ultrasound, 131 I neck scintigraphy and radioiodine uptake. Posttherapy whole body scan (WBS) was acquired after 4-6 days. Ablation was assessed after 6-12 months by WBS, Tg and TgAb following L-thyroxine withdrawal. Methods: Group A: preparation by L-T 4 withdraw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(45 citation statements)
references
References 12 publications
1
41
0
3
Order By: Relevance
“…Use of recombinant human TSH is probably the best solution to avoid hypothyroidism. Studies have found thyroid hormone withdrawal and rhTSH approaches to be equally effective in preparing patients for remnant ablation [55][56] or diagnostic examination. However, it is expensive and not readily available in our institution.…”
Section: E) What Is the Role Of Recombinant Human Tsh (Rhtsh)?mentioning
confidence: 99%
“…Use of recombinant human TSH is probably the best solution to avoid hypothyroidism. Studies have found thyroid hormone withdrawal and rhTSH approaches to be equally effective in preparing patients for remnant ablation [55][56] or diagnostic examination. However, it is expensive and not readily available in our institution.…”
Section: E) What Is the Role Of Recombinant Human Tsh (Rhtsh)?mentioning
confidence: 99%
“…However, recent publications have shown that 50 mCi 131 I is equally effective to 100 mCi 131 I for thyroid remnant ablation following rhTSH, with no interruption in L-T 4 administration (33,34). The use of rhTSH for ablation has shown to produce lesser exposure of radioiodine to the bone marrow and lowered toxicity related to the radioiodine dose than when administered after withdrawal (35,36).…”
Section: Postoperative Radioiodine Administrationmentioning
confidence: 99%
“…According to the American Thyroid Association (ATA) and European Thyroid Association (ETA) guidelines (1, 2), sufficient evidences have been accumulated indicating that in low-risk patients who are candidates for thyroid ablation, low RAI activities between 1100 and 1850 MBq have similar ablative effects (3,4,5,6,7,8,9,10,11) and similar (very low) recurrence rates during follow-up (12,13). Very recently, this concept has been reinforced by two prospective, randomized, multicenter studies (14,15), which compared the effectiveness of RAI ablation using 1110 or 3700 MBq of 131 I.…”
Section: Introductionmentioning
confidence: 99%